2018
DOI: 10.1016/j.psyneuen.2017.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Maternal prenatal stress and placental gene expression of NR3C1 and HSD11B2: The effects of maternal ethnicity

Abstract: These results support previous findings of an association between maternal prenatal stress and the expression of placental genes associated with the HPA-axis, but only in Caucasians. These ethnic specific findings are novel and require replication in different populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 47 publications
4
34
2
2
Order By: Relevance
“…15,16 There is some evidence that ethnicity may play a role in how the placenta reacts to stress and therefore how this affects the developing fetus; for example, stress-related expression of the placental genes that regulate cortisol in the placenta was found in Caucasian women only. 17 Developing countries have the highest rates of DV, especially those in Africa. 15,18 This could be due to civil conflict as the 40% of countries in sub-Saharan Africa that have seen conflict have significantly higher rates of DV.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 There is some evidence that ethnicity may play a role in how the placenta reacts to stress and therefore how this affects the developing fetus; for example, stress-related expression of the placental genes that regulate cortisol in the placenta was found in Caucasian women only. 17 Developing countries have the highest rates of DV, especially those in Africa. 15,18 This could be due to civil conflict as the 40% of countries in sub-Saharan Africa that have seen conflict have significantly higher rates of DV.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Intimate partner or domestic violence is commonplace globally, an exposure more common than some other maternal health conditions more routinely checked for in prenatal screenings and is highly prevalent across both developed and developing countries, across ethnic groups and thought to be particularly common during pregnancy . There is some evidence that ethnicity may play a role in how the placenta reacts to stress and therefore how this affects the developing fetus; for example, stress‐related expression of the placental genes that regulate cortisol in the placenta was found in Caucasian women only . Developing countries have the highest rates of DV, especially those in Africa .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, levels of foetal cortisol during maternal stress are difficult to assess and the relationship between maternal and foetal cortisol can vary as a function of placental 11 beta-hydroxysteroid dehydrogenase 2 (HSD11B2) and P-glycoprotein levels (P-gp) 7 ( Figure 1). 73 Interestingly, previous rodent studies have shown that chronic prenatal stress results in increased DNA methylation at multiple CpG sites within the placental Hsd11b2 gene promoter, resulting in a down-regulation of placental transcription. 71 By contrast, sGC represent a poor substrate for HSD11B2, and so are not readily metabolised.…”
Section: Mechanis Ms Of Maternal Prog R Ammingmentioning
confidence: 99%
“…72 Recently, maternal prenatal stress has been associated with a down-regulation of placental HSD11B2, and that this effect is dependent on maternal ethnicity. 73 Interestingly, previous rodent studies have shown that chronic prenatal stress results in increased DNA methylation at multiple CpG sites within the placental Hsd11b2 gene promoter, resulting in a down-regulation of placental transcription. 74 This increase in methylation was associated with an increase in placental expression of Dnmt3a (DNA methyltransferase 3 alpha), an enzyme responsible for de novo DNA methylation.…”
Section: Mechanis Ms Of Maternal Prog R Ammingmentioning
confidence: 99%
“…Other studies have shown a dose response relationship between exposure to prenatal risk factors (including maternal depression), fearless temperament in early childhood and the development of offspring conduct problems and callous unemotional traits in adolescence [30]. As the human literature develops, complex biological and epigenetic mechanisms are discovered with sex-specific and ethnicity-specific effects reported [31,32]. Whilst it is recognised that the association between maternal depression and adverse offspring outcomes at least in part reflects shared genetic risk, genetically informative designs have shown that both genetic and environmental mechanisms contribute to the elevated risk of antisocial behaviour among the offspring of depressed parents [14,33].…”
Section: Introductionmentioning
confidence: 99%